2013 Asilomar Conference on Signals, Systems and Computers 2013
DOI: 10.1109/acssc.2013.6810685
|View full text |Cite
|
Sign up to set email alerts
|

Generalized linear minimum mean-square error estimation with application to space-object tracking

Abstract: The linear minimum mean-square error (LMMSE) estimation has been shown to provide a good tradeoff between the computational requirement and estimation accuracy in nonlinear point estimation. However, the best estimator within the linear class may not be adequate to provide acceptable accuracy when dealing with a highly nonlinear problem. A generalized LMMSE (GLMMSE) estimation framework searches for the best estimator among all the estimators that are linear in a vector-valued function (namely, measurement tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The state of the art (Liu et al, 2013;Lan and Li, 2015) has demonstrated that proper 'uncorrelated conversion' of the nonlinear measurement can mine more information from the measurement information for better filtering accuracy, compared to the original measurement. This leads to an updating protocol which is based on linear combination of the original measurement and its uncorrelated conversions.…”
Section: Converted Measurement Filteringmentioning
confidence: 99%
See 1 more Smart Citation
“…The state of the art (Liu et al, 2013;Lan and Li, 2015) has demonstrated that proper 'uncorrelated conversion' of the nonlinear measurement can mine more information from the measurement information for better filtering accuracy, compared to the original measurement. This leads to an updating protocol which is based on linear combination of the original measurement and its uncorrelated conversions.…”
Section: Converted Measurement Filteringmentioning
confidence: 99%
“…More implementations for iterated/repeated observation (or its conversion) updating have been realized on different Gaussian filters (Zhan and Wan, 2007;Zanetti, 2012;Steinbring and Hanebeck, 2014;Huang et al, 2016b). These have a close connection to the concepts of progressive correction (Oudjane and Musso, 2000) and progressive Bayes (Hanebeck et al, 2003), both of which strive to apply Bayes updating in a progressive manner and aforementioned uncorrelated augmentation (Liu et al, 2013;Lan and Li, 2015;. In fact, the idea of emphasizing the observation when it is very informative has also inspired the development of random-sampling based filters such as annealed/unscented PFs (van der Merwe et al, 2000;Godsill and Clapp, 2001), particle flow filter (Daum and Huang, 2010), and feedback PF (Yang et al, 2016), and some (re)sampling approaches (Li et al, 2015a;.…”
Section: Very Informative Observationmentioning
confidence: 99%
“…As shown in [24], the GLMMSE outperforms the LMMSE estimators. Thus, in S1 the UCF and the OUCF are compared with the LMMSE estimator of [30] and the GLMMSE estimator of [24].…”
Section: Simulation Resultsmentioning
confidence: 86%
“…As shown in [24], the GLMMSE outperforms the LMMSE estimators. Thus, in S1 the UCF and the OUCF are compared with the LMMSE estimator of [30] and the GLMMSE estimator of [24]. Because the LMMSE and the GLMMSE both use the transformed measurement z k = [r k cos(θ k ), r k sin(θ k )] T , the UCF and the OUCF also use this transformed measurement for a fair comparison.…”
Section: Simulation Resultsmentioning
confidence: 86%
See 1 more Smart Citation